Relevansi Pandangan William Gouge Mengenai Tanggung Jawab Orang Tua Dan Anak Terkait Disiplin Dalam Keluarga - Yuki Fransiska; Jadi S. Lima (STTRII, 2020)
Discipline for children in the family has presented a dilemma between two extremes which keep repeating ranging from violence to neglect. Similar dilemma is also faced by Christian families in Indonesia. Therefore, this essay seeks to describe and re-analyze the relevance of William Gouge’s view on the concept of discipline for children, one of the Puritans, to be considered as an alternative concept of discipline for children in Christian families today in Indonesia. Specially, this article concerned about the responsibilities of parents and children in discipline. This study concludes that Gouge’s view is relevant and make a possible for a balance of discipline.